Moving beyond Integrated Water Resources Management: Developmental Water Management in South Africa - van Koppen, Barbara; Schreiner, B. (Informa UK Limited, 2014)
This article traces the history of integrated water resources management (IWRM) in South Africa since the 1970s. It examines IWRM according to its three common pillars, which are also reflected in South Africa's National Water Act: economic efficiency, environmental sustainability, and equity. The article highlights how the principles of economic efficiency and the environment as a user in its own right emerged under apartheid, while equity was only included in the post-1994 water policies, with evolving influence on the other two principles. In 2013, the Department of Water Affairs overcame the widely documented flaws of IWRM by adopting developmental water management as its water resource management approach, aligning with the political and socio-economic goals of South Africa's democratic developmental state.